2021
DOI: 10.3390/ijerph18179177
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Unmet Healthcare Needs of Older People: Did Inequity Arise in Europe?

Abstract: Background: The disruption in healthcare provision due to the COVID-19 pandemic forced many non-urgent medical treatments and appointments to be postponed or denied, which is expected to have huge impact on non-acute health conditions, especially in vulnerable populations such as older people. Attention should be paid to equity issues related to unmet needs during the pandemic. Methods: We calculated concentration indices to identify income-related inequalities and horizontal inequity in unmet needs due to pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Furthermore, the current COVID-19 pandemic may further exacerbate the difficulties in accessing a regular medical doctor and addressing unmet healthcare needs among Canadians, as in-person clinic visits may have been limited during this period, and some individuals may have also been reluctant to attend appointments due to fear of exposure to COVID-19. 35,36 When exploring reasons for not having a regular medical doctor, the province-specific analysis revealed that no doctor was available in the area was one of the main reasons, as shown in Appendix A. Respondents also reported two additional reasons for not having a regular medical doctor: doctors were not taking new patients; and respondents did not try to contact one. The latter reason illustrates the need to invest in advocacy and education efforts surrounding the potential health benefits of having a regular medical doctor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current COVID-19 pandemic may further exacerbate the difficulties in accessing a regular medical doctor and addressing unmet healthcare needs among Canadians, as in-person clinic visits may have been limited during this period, and some individuals may have also been reluctant to attend appointments due to fear of exposure to COVID-19. 35,36 When exploring reasons for not having a regular medical doctor, the province-specific analysis revealed that no doctor was available in the area was one of the main reasons, as shown in Appendix A. Respondents also reported two additional reasons for not having a regular medical doctor: doctors were not taking new patients; and respondents did not try to contact one. The latter reason illustrates the need to invest in advocacy and education efforts surrounding the potential health benefits of having a regular medical doctor.…”
Section: Discussionmentioning
confidence: 99%
“…They also noticed substantial variations in having difficulty in accessing medical care in the evenings, weekends, and after hours across the provinces and territories, which has the potential to significantly contribute to unmet healthcare needs among the residents of these provinces. Furthermore, the current COVID‐19 pandemic may further exacerbate the difficulties in accessing a regular medical doctor and addressing unmet healthcare needs among Canadians, as in‐person clinic visits may have been limited during this period, and some individuals may have also been reluctant to attend appointments due to fear of exposure to COVID‐19 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, this legislative review is taking place against the background of the COVID outbreak, lending particular significance to the topic of UMN—with the surprise element in the speed, scope and scale of that pandemic still resonating across Europe and around the world. The recent declaration of monkeypox as a major health threat only adds to the importance of the debate [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although Poland has adopted many preventive strategies and implemented many international recommendations to combat the SARS-CoV-2 pandemic (e.g., preventive measures, maintaining social distancing, early case detection and isolation of patients, testing, epidemic surveillance, protection of high-risk groups, travel control, international cooperation and exchange of experiences public education, a vaccine policy, and many more) [10], there is still much to be improved. Results presented by González-Touya et al suggest that "Poland, Italy and Greece should pay attention to possible equity problems regarding denied medical care that arose during the first months of the pandemic" [11]. Delays in diagnosis and treatment, especially in elderly patients, may ultimately translate into adverse health outcomes, reduced quality of life, and even widen socioeconomic health inequalities, which will impact a growing share of the European population in the next decades [11].…”
Section: Introductionmentioning
confidence: 99%
“…Results presented by González-Touya et al suggest that "Poland, Italy and Greece should pay attention to possible equity problems regarding denied medical care that arose during the first months of the pandemic" [11]. Delays in diagnosis and treatment, especially in elderly patients, may ultimately translate into adverse health outcomes, reduced quality of life, and even widen socioeconomic health inequalities, which will impact a growing share of the European population in the next decades [11].…”
Section: Introductionmentioning
confidence: 99%